Responses of Aquatic Saproxylic Macroinvertebrates to Reduced-Impact Logging in Central Amazonia - Roque, Fabio O.; Escarpinati, Suzana Cunha; Valente-Neto, Francisco C.; Hamada, N. (Neotropical Entomology, 2015)
Reduced-impact logging (RIL) is an alternative land use because it reduces damage to forest cover in comparison with clear-cut practices. However, management practices adopted in RIL can affect wood availability and, consequently, fauna associated with dead wood during part of their life cycle (saproxylic). In this study, we evaluated whether aquatic saproxylic macroinvertebrates are affected by reduced-impact logging in Central Amazonia. We selected six streams in areas under reduced-impacted logging and six in primary forest areas and collected submerged woody debris. We did not find any differences in water pH, conductivity, and wood availability between reduced-impacted forest and primary forest streams. We found 248 saproxylic aquatic macroinvertebrates belonging to 37 taxa. We found five wood specialist (Dryops, Lutrochus, Stenochironomus, Oukuriella, and Endotribelos) and 32 generalists, totalling 98 and 150 individuals, respectively. In general, our results show that reduced-impact logging does not affect richness, abundance, and composition of saproxylic macroinvertebrates. The main explanation for this pattern is that management practices do not change important macroinvertebrate niche dimensions, including wood availability and the water’s chemical and physical variables. Thus, controlled logging, such as applied in the area of the Central Amazonian streams studied, opens a new prospect for insect conservation and commercial exploitation of wood, which is not possible when clear-cut practices are adopted. © 2015, Sociedade Entomológica do Brasil.
Keywords: Dryops; Endotribelos; Hexapoda; Lutrochus; Stenochironomus; Animals; Classification; Ecosystem; Environmental Protection; Invertebrate; Physiology; River; Wood; Animal; Conservation Of Natural Resources; Ecosystem; Invertebrates; Rivers; Wood